Penerapan Strategi Ruang Tenang untuk Mengurangi Perilaku Tantrum Anak di Kelompok Bermain - Eli Desni; Nurhafizah (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research is driven by the phenomenon of tantrum behavior in early childhood within Playgroup settings, which often arises due to limitations in emotional regulation and verbal communication skills. The primary objective of this study is to analyze the application of the calm corner strategy in addressing children's tantrum behavior in the school environment. The method employed is Classroom Action Research (CAR), conducted in two cycles comprising planning, action, observation, and reflection stages. The research subjects consisted of 8 children in a playgroup who exhibited tantrum behavior. Data were collected through descriptive observation, field notes, and documentation. Data were analyzed using descriptive qualitative analysis by comparing the observation result from the pre-cycle, cycle 1, and cycle 2 to identify chabges in children’s tantrum behavior. The results indicate that the use of a calm corner, equipped with sensory media and supported by persuasive teacher guidance, is effective in reducing the frequency of tantrums. The success percentage increased from 37,5% in the pre cycle, to 62,5% in cycle 1, and increased again to 87,5% in cycle 2. This strategy trains children to recognize and manage their emotions independently without resorting to punishment. The success of this intervention relies heavily on the teacher's self-management skills and consistent collaboration between the school and parents in providing a unified understanding of children's emotional regulation.